Explaining Germany's Electoral Geography: Evidence from the Eastern States. Issue 1 (1st March 2019) - Wuhs, Steven; McLaughlin, Eric
Abstract : Partisan attachments and voting behavior in Germany today are more volatile than in the past. This article tests the enduring influence of social cleavages on voting relative to two other factors that account for party performance: path dependent forces and spatial dependence. Drawing on original data from the eastern German states, we explain support for Germany's main parties in the 2017 federal election. We find relatively weak evidence for continued influence of social divisions for the major parties, but that support for the radical right Alternative for Germany (AfD) did reflect underlying cleavage structures. Additionally, we identify reliable effects of the historical immigrant population on contemporary voting. We also see weak evidence of lock-in political effects associated with German reunification, limited only to the CDU. Most interestingly, we observe powerful and robust effects of spatial dependence for three of the four parties we examine. We conclude that the effects presented here should signal to scholars of parties and electoral politics the need to incorporate history and geography into their analytical frameworks alongside more traditional approaches, since eastern Germany may in fact be less spatialized than western Germany or other country cases because of the homogenizing efforts of the SED regime.